Simple and Efficient Computer Algorithm to Solve Radial Distribution Networks - RANJAN, RAKESH; DAS, D (2003)
A simple and efficient algorithm is presented to solve radial distribution networks (RDN). It solves the simple algebraic recursive expression of voltage magnitude and all the data are stored in vector form. The algorithm uses the basic principle of circuit theory and can be easily understood. The proposed algorithm has been tested with several distribution networks and results are compared with two other existing methods. The effectiveness of the proposed algorithm is demonstrated through two examples.